Effect of Animated Video Media on Creative Thinking in Elementary School IPAS (Natural and Social Sciences) Learning - Mariam, Devi; Harmawati, Harmawati; Sa’diah, Tia Latifatu (PT. Riset Press International, 2024)
This study aims to explore how animated video media affects students' creative thinking in IPAS (Natural and Social Sciences) education. To achieve this, researchers used a preexperimental design with a static group comparison approach. This design involves two groups of students: one that is exposed to the animated video media (experimental group) and another that is not (control group). The study included two key assessments: a pretest (O1) conducted before the introduction of the animated video media, and a posttest (O2) administered after the intervention. These tests were designed to measure changes in students' creative thinking abilities. The focus of the research is on how animated video media can enhance creative thinking within IPAS learning, particularly in the area of social studies at the elementary school level. By comparing the results of the pretest and posttest, the study aims to evaluate the effectiveness of animated video media in fostering creativity in students' social studies education.